1980
DOI: 10.1111/j.1438-8677.1980.tb01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Life Forms and Life Strategies in Nanocyperion Communities From the Netherlands Frisian Islands

Abstract: SUMMARYNanocyperion communities (s.l.) are considered here as "warp-and-woof" communities;the Nanocyperion components are described separately as synusiae. On

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This dynamical view on species life history deviates from several other strategy concepts. For instance, it is different from the Ôwarp and woofÕ strategy concept proposed by During (1980) for dwarf-rush species. The sudden emergence of Gentiana and Rhynchospora would be the ÔwoofÕ, and the poor, bare sand surface after inundation the ÔwarpÕ (cf.…”
Section: A Dynamical View On Life History Strategiesmentioning
confidence: 85%
“…This dynamical view on species life history deviates from several other strategy concepts. For instance, it is different from the Ôwarp and woofÕ strategy concept proposed by During (1980) for dwarf-rush species. The sudden emergence of Gentiana and Rhynchospora would be the ÔwoofÕ, and the poor, bare sand surface after inundation the ÔwarpÕ (cf.…”
Section: A Dynamical View On Life History Strategiesmentioning
confidence: 85%
“…Typical representatives are very small plants, usually between 2 and 10 cm, which can complete their life cycle within a few months. Natural growth sites of these species are neutral to slightly acid, more or less nutrient-poor soils at river banks, lake shores, and trampled sites (Pietsch 1973;During 1980;Müller & Gebhardt 1998). These sites are characterized by a soil texture with a high proportion of small particles, which enhance the water storage capacity and capillary rise of groundwater, but reduce soil pore water availability (Bagi 1991).…”
Section: Introductionmentioning
confidence: 99%
“…On sites with repeated disturbance, such as road-verges, their presence has a more permanent character. It is generally thought that this behaviour is a consequence of the lack of competition for nutrients and/or light from taller species (Pietsch 1973;During 1980). However, Bonis et al (1997) found that fresh gaps in chalk grassland were too poor in phosphorus for colonization by short-lived pioneer plant species.…”
Section: Introductionmentioning
confidence: 99%
“…An obvious explanation is that the water level in spring is a key factor. In dry periods this level is low, leaving a broad shore area for germination of annual species, while in wet periods these areas are under water and therefore less rich in species during the summer (During 1980). However, the scenario study shows that the effects of increasing precipitation will be limited.…”
Section: Discussionmentioning
confidence: 94%